Plantation agroforestière d'Acacia auriculiformis dans le Haut-Katanga. Guide technique - Doucet, Jean-Louis (Uliège Library, 2017)
Agroforestry is a sustainable soil management method. It associates in time or space trees with crops and/or livestock. Thanks to this association, positive interactions are created between the different components of the system. For example, the introduction of nitrogen-fixing trees benefits food crops by playing the role of green manure. Agroforestry of trees in a crop plot also brings other benefits: - they facilitate the penetration of water into the soil, - they help fight erosion, - they draw nutrients from deep within the soil and make them available on the surface for crops, - they play the role of windbreaks, - they can provide shade in the dry season, - they can provide edible fruits, honey, timber, fuelwood, medicinal products, etc. Agroforestry is the focus of the "Agroforests for Kipushi Development" project, AFODEK, which was implemented between December 2012 and November 2017 with financial support from the European Union (DCI-FOOD/2012/294-526). Based on the experience of the Hanns Seidel Foundation in Mampu (Plateaux Batékés), three organizations, GRET, the Belgian non-profit organization Nature+ and the Centre Promotionnel du Paysannat, joined their efforts to develop an agroforestry perimeter of 2,000 hectares (ha) in an area of degraded savannahs with poor soil fertility. This technical document has been prepared by the AFODEK project to share the experience of the Kipushi agroforestry perimeter. It is intended primarily for a public of farmers or agricultural technicians. / L'agroforesterie est un mode de gestion durable des sols. Elle associe dans le temps ou dans l'espace des arbres avec des cultures et/ou l'élevage. Grâce à cette association, des interactions positives se créent entre les différentes composantes du système. Par exemple, l'introduction d'arbres fixateurs d'azote bénéficie aux cultures vivrières en jouant le rôle d'engrais vert. L'agroforesterie d'arbres dans une parcelle de culture apporte également d'autres avantages : - ils facilitent la pénétration de l'eau dans le sol, - ils permettent de lutter contre l'érosion, - ils puisent les éléments nutritifs en profondeur et les rendent disponibles en surface pour les cultures, - ils jouent le rôle de brise-vent, - ils peuvent apporter de l'ombrage en saison sèche, - ils peuvent fournir des fruits comestibles, du miel, du bois d'oeuvre, du bois de chauffe, des produits médicinaux, etc. L'agroforesterie est au coeur du projet "Agroforêts pour le développement de Kipushi", AFODEK, qui a été mis en oeuvre entre décembre 2012 et novembre 2017 grâce au soutien financier de l'Union européenne (DCI-FOOD/2012/294-526). S'appuyant sur l'expérience de la Fondation Hanns Seidel à Mampu (Plateaux Batékés), trois organismes, le GRET, l'asbl belge Nature+ et le Centre Promotionnel du Paysannat ont joint leurs efforts pour aménager un périmètre agroforestier de 2000 hectares (ha) dans une zone de savanes dégradées aux sols peu fertiles. Le présent document technique a été élaboré par le projet AFODEK en vue de partager l'expérience du périmètre agroforestier de Kipushi. Il s'adresse avant tout à un public d'agriculteurs ou de techniciens agricoles.